Improving Tissue Box Decorating Skills Through Task Analysis for Children with Mild Mentally Retarded Child: (Class Action Research at SLB Luak Nan Bungsu) - Faiza Sukma; Martias Z (Yayasan Citra Dharma Cindekia, 2022)
Conducting this research was hampered by the fact that, although Luak Nan Bungsu SLB had learned how to decorate tissue boxes in grade VII, some children lacked the necessary skills and scored below the KKM. This study uses task analysis to discuss how to make it easier for mild mentally retarded children to decorate tissue boxes made from banana stems. By using classroom action research (CAR), this research was conducted in two cycles, with each cycle consisting of: preparing, implementing, observing, and reflecting. Observation, documentation, and action tests were the methods used to collect data. The EM value in the first cycle of action was 55.88%, and in the second cycle was 88.23%. DT children scored in cycle I, namely 52.94%, and children II, scored in cycle I, namely 85.29 percent. The results were obtained by the children using two cycles of improving their abilities.